Upaya Meningkatkan Kecerdasaan Visual Spasial Anak Usia Dini Melalui Media Pop-Up Book (Buku 3 Dimensi) - Keyla Al-Khaira; Khadijah Khadijah (LPPM Institut Nasional Laa Roiba Bogor, 2023)
Thisexpects to decide the impact of spring up book media on visual spatial insight of youth at RA Al-Khairiyah, jln. T.S.Mohd. Chapter No. 52: Pantai Gemi Kec Kab Stabat Langkat. Classroom action research employing a qualitative method is this kind of research. The subjects in this study were youngsters matured 4-6 years with a sum of 20 kids comprising of 7 young men and 13 young ladies. Interviews, observation, documentation, and tests are used to collect data. The subjective legitimacy test procedure in this review utilized source triangulation and specialized triangulation. The consequences of this study show that the utilization of spring up learning media can work on kids' Visual and Spatial Knowledge in concentrating for 12-14 minutes, retelling in a straightforward way. According to this description, children aged 4-5 at RA Al-Khairiyah, jln can benefit from using pop-up learning materials to improve their spatial and visual reasoning skills. T.S.Mohd. Chapter No. 52: Pantai Gemi Kec Kab Stabat Langkat. Keywords: visual spatial intelligence, pop-up books, and early childhood